The changes of tissues components of the anterior abdominal wall of rats after plasty of considerable ventral defect - Malkov I.I. (Морфологія, 2008)
The quantitative morphological estimation of changes in microcirculatory, connective tissue and muscle-aponeurotic components of the anterior abdominal wall of rats were made after the alloplasty of considerable ventral defect by the polypropylene monofilament net "Prolene". Histological study was carried out in 3 days, 10 days, 1 month, 3 months and 1 year after implantation of polypropylene prosthetic device. 68 rats were distributed in 3 experimental groups: 1) the plasty by pull and approximation of wound edges with the layer by layer wound closure; 2) the plasty by the fixation of polypropylene monofilament net "Prolene" with the subsequent pull and approximation of defect edges; 3) the plasty by the fixation of net without the subsequent pull and approximation of defect edges. It was revealed that mechanical tension of muscle-aponeurotic layer of abdominal wall during the pull and approximation of experimental defect edges is a substantial factor which increases the terms of scarring, and also causes the permanent degenerative processes in muscle-aponeurotic structures. It is accompanied by the deficit of microcirculatory supplement of structures, the dystrophic changes in muscular fibres, hyperplasia of connective tissue components of muscle-aponeurotic layer of anterior abdominal wall with the most prominent pathological changes from 10th day to the end of 3th month after alloplasty. Application a polypropylene net for the plasty without mechanical tension of muscle-aponeurotic structures optimizes the recovery and adaptation processes during the first 3 months after operation.